Relationship between fall risks and activities of daily living in older individuals - Arli Senay Karadag; Yildiz Metin; Bakan Ayse Berivan (Sciendo, 2020)
To investigate the relationship between fall risks and maintaining activities of daily living in individuals aged 65 and over.